Private Investment and Endogenous Growth : Evidence From Cameroon - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 1997)
This paper investigates empirically the factors that have influenced economic growth in Cameroon during 1963-96. The results, which support the endogenous-growth-type model, indicate that (1) the aggregate production function exhibits increasing returns to scale; (2) the impact of increases in private investment on growth is large, significant, and robust; (3) increases in government investment have a positive impact on growth; (4) human capital development plays an important role in output expansion; (5) positive externalities are generated by physical and human capital accumulation; and (6) growth is boosted by economic policies that foster external competitiveness and a prudent fiscal stance.